From the lagoon-city to the lagoon of adaptive cities: Methodological approach to support trans-municipal and multilevel governance for climate adaptation in the Venice lagoon - Magni, Filippo; Lucertini, Giulia; Federico, Katia (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The impacts of climate change and the increasing occurrence of consequent extreme events in recent years have led to significant environmental, social and economic consequences in a fragile and highly vulnerable territory such as Venice. It is precisely in this perspective, which considers areas particularly vulnerable to the effects of climate, that the scientific research program Venezia2021, coordinated by CORILA - Consortium for coordination of research activities concerning the Venice lagoon system, is inserted. The research in question involves a complex process of identification and integration of innovative tools, data processing and analysis and assessment of impacts, in order to contribute to the maintenance of a proper balance of the lagoon ecosystem in a perspective of increased climate resilience. The overall objective of the research was to build a strategic, accurate and shared vision with respect to the challenges that await the preservation of the city and its lagoon, (a World Heritage Site), in consideration of climate change scenarios. Specifically, this paper analyzes the research experience of thematic axis No. 5 that led to the drafting of the Climate Change Adaptation Plan for the Venice Lagoon. The operational path that led to the construction of the plan was guided by an in-depth spatial study and development of an integrated system of analysis, assessment, planning, management and monitoring of the Venetian area capable of supporting the city and the activities that operate in it, through coordinated adaptation actions aimed at increasing sustainability and resilience as a whole.